Source of information on sexual and reproductive health among secondary schools’ girls in the Klang Valley. - Kamrani, Mahnaz Akbari; Syed Yahya, Sharifah Zainiyah; Ahmad, Zaiton; Hamzah, Azimi (Malaysian Public Health Specialist Association, 2011)
Adolescents are known to obtain information regarding sexual and reproductive health from a variety of sources and not just during formal lessons in schools. This cross-sectional descriptive study was carried out to determine the source of information on sexual and reproductive health among Form four secondary schools girls in the Klang Valley as well as parents’ relationship profile. A total of 520 secondary school girls were recruited for the study. In this study, the source of information on puberty and sexual topics were categorized as follows: first level of importance – mothers, second level of importance – siblings, third level of importance – fathers, fourth level of importance – friends, fifth level of importance – teachers and sixth level of importance – books/internet. A majority of respondents agreed that their mothers were the first level of importance they sought for information on puberty (74.8%) and sexual topics (53.8%). Thirty nine point three percent (39.3%) of respondents reported it was very easy to have a dialogue with their mothers while only 10.0% of the respondents said it was very easy to have a dialogue with their fathers. While this was the case, only 6.3% of the respondents reported discussing sex-related matter with their mothers.